Adopting Interactive Content in Language Education: A Review of Literature - Umi Kalsom, Masrom; Mardiana, Idris; Zailani, Jusoh; Wan Noor Farah, Wan Shamsuddin (European Publisher, 2023)
The digitalisation of teaching is a reality to which we must adapt. In order to successfully design effective instructional design for learners, one must have competency in designing digital tools that are suitable for learners. This study reviewed papers published from 2005 to 2022 on interactive content particularly in teaching and learning context. A total of 32 research articles were reviewed to achieve the research purposes. The focus of this paper is on the type of interactive content applied in lessons, learners’ and instructors’ feedback on the use of interactive content, ways to design interactive content and its instructional design and finally the impacts of interactive content on higher education landscape. A discussion based on the results, followed by implications for future research directions and conclusions are also presented. This study is relevant as it provides in depth understanding on how interactive content can be better adapted in the future.